Managing Financial Integration and Capital Mobility—Policy Lessons from the Past Two Decades. Issue 4 (15th August 2013) - Aizenman, Joshua; Pinto, Brian
Abstract Emerging market experience over the past two decades has revealed the tenuous links between external financial integration and faster growth, and the proclivity of such integration to fuel costly crises. Emerging markets learned, converging to the middle ground of the macroeconomic trilemma. Following their crises of 1997–2001, emerging markets added financial stability as a goal, self‐insured by building up international reserves, and adopted a public finance approach to financial integration. The global crisis of 2008–09 illustrated that the advanced economies "overshot" the optimal degree of financial deregulation, while the resilience of the emerging markets validated their public finance approach to financial integration.